Perancangan Sistem Informasi Manajemen Rantai Pasok Minyak Sawit Mentah Berbasis GIS - Ringgo Afrinando (Jurnal Optimasi Sistem Industri, 2012)
This study discusses about information systems of CPO supply chain management in PTPN 6 Ophir. PTPN 6 management still use the conventional system (archival documents) in running their business. This information is not yet integrated with the map of plantation, so it will allow errors and inaccuracies in the planning, management and maintenance of oil palm plantations. Otherwise, the output from the production and processing of FFB to CPO and Palm Kernel also has not been well managed. So this would have difficulties in data storage on the the plantation and harvest information and to make decision for the FFB receiving division and distribution of CPO and Palm Kernel. Therefore needed a system that can control the activities in the oil palm plantation and processing by utilizing information technology system that integrates mapping and data information in a software that will facilitate decision making for planning and maintenance. The stages of the study consist of preliminary study, the selection method of problem solving, designing model system, database and software design and verification and validation of the model system. The study used primary data and secondary data. The primary data includes interviews about the company's business processes and the mechanisms of oil production. Secondary data includes administrative forms such as SPB, form the collection of FFB, weight measurement form and daily report sheet of factory. Model systems in the information system design used Object Oriented Analysis and Design method. This method will considers and designing systems with focusing the objects associated with the system. Verification results of the design has been done by using the method of Computerized Model Verification. This method to see whether the information system has been designed to run properly with the conceptual model of the system. Validation has been done by using Operational Validity. Validity Operational techniques used Black Box Test Method or directly test by the person that understand the issues in study. The results was Information System Software Design of CPO Supply Chain Management at PTPN 6 already integrates all data and information on the plantation, processing and marketing of CPO and palm kernel oil in a web-based application with support for spatial data processing in online mapping format. The system model can be seen through the business process diagram, use case diagram, class diagram and entity relationship diagram.